Female adolescents’ knowledge on cervical cancer screening and immunization (2015)
Context and purpose: Although the new infections of human papilloma virus (HPV) can be acquired at any age, women’s less than 25 years predominated. The present study investigated the knowledge of school adolescents on prevention and screening of cervical cancer. Method: In a cross-sectional study, 240 female adolescents (aged 15-20 years) randomly enrolled using a multistage sampling technique in four peri-urban schools, were interviewed in Ibandan, Nigeria. Survey questions addressed terminology and general knowledge of cervical cancer screening and immunization. Results: The overall response rate was 83.3%. 54.4% of the respondents did not know that screening for HPV is important and available for all females. 82.5% indicated that the HVP vaccines are not for females of age less than 15 years. Conclusion: More than half female adolescents in this survey had poor knowledge of cervical cancer screening and immunization and this has serious implications for school health and safety education as well as cervical cancer prevention programmes.